Synthesis of aromatic stigmastanes: Application to the synthesis of aromatic analogs of brassinosteroids - Acebedo, Sofía Lorena (2012)
In this paper, we report the first synthesis of aromatic analogs of brassinosteroids. In order to accomplish this task, we explored two different synthetic approaches, which involved demethylation of the C-19 of stigmasterol to yield A-ring aromatic 3-hydroxystigmastanes. One of the new aromatic analogs showed a reduced but significant bioactivity when compared to the natural hormones.